STRATEGI MENCARI PASANGAN DALAM PEMBELAJARAN APRESIASI PUISI SISWA SM - Supriadi, Supriadi (Indonesian Journal of Educational Studies, 2015)
This study aims to describe the learning poetry appreciation with junior high school students looking for a partner strategy. This study used experimental design. The results showed the is a significant difference between the students' ability to appreciate poetry with a couple looking strategy (make a match) with the conventional strategy. This is evident in the average value and completeness. The average value of the control class Â ie 70.72; the experimental class higher at 88.26. Moreover, the differences seen in the results of the t test analysis showed that the value of 14.497 t count> t table 1.68 to 0.05.